2020
DOI: 10.1038/s41467-020-15698-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for active single and double ring complexes in human mitochondrial Hsp60-Hsp10 chaperonin

Abstract: 3,4 ✉ mHsp60-mHsp10 assists the folding of mitochondrial matrix proteins without the negative ATP binding inter-ring cooperativity of GroEL-GroES. Here we report the crystal structure of an ATP (ADP:BeF 3 -bound) ground-state mimic double-ring mHsp60 14 -(mHsp10 7 ) 2 football complex, and the cryo-EM structures of the ADP-bound successor mHsp60 14 -(mHsp10 7 ) 2 complex, and a single-ring mHsp60 7 -mHsp10 7 half-football. The structures explain the nucleotide dependence of mHsp60 ring formation, and reveal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 68 publications
4
67
0
Order By: Relevance
“…Also S488, corresponding to S462 in mHsp60, which has been recently reported to be involved in inter-ring contacts (Gomez-Llorente et al, 2020), was found to be replaced by a threonine ( Table 1 and Supplementary Table S1). The important role of this amino acid suggests a potential deleterious effect of its substitution.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Also S488, corresponding to S462 in mHsp60, which has been recently reported to be involved in inter-ring contacts (Gomez-Llorente et al, 2020), was found to be replaced by a threonine ( Table 1 and Supplementary Table S1). The important role of this amino acid suggests a potential deleterious effect of its substitution.…”
Section: Discussionmentioning
confidence: 86%
“…The residues Asp504, Ala505, and Met506 are located in the nucleotide-binding pocket of hHsp60, as inferred from the solved crystal structures (Nisemblat et al, 2015;Gomez-Llorente et al, 2020). The corresponding amino acids in GroEL, i.e., Asn479, Ala480, and Ala481, involved in nucleotide binding (Boisvert et al, 1996;Xu et al, 1997;Brocchieri and Karlin, 2000), have different identities, but maintain the same location in proteins three-dimensional structures (Figures 1, 2G-I).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations